Debris flows and energy dispersers in the Juan Carossio Chosica torrent - Lima - Gallarday Bocanegra, Tomás (2014)
The basin of the Juan Carossio gorge has a width of approximately 15 meters, with a length of 1,308.29 meters, giving a collection area of ​​around 2 km2. It is limited in the upper part by the 1,308.29 m elevation, and in the lower part with delivery to the Rímac river at 900 m elevation. Longitudinally, three small receiving streams (torrent, with an average gradient greater than 30%) have formed in the upper central zone, which downstream unite into one, still with a strong gradient, also receiving the water that led it (originally) to the Rímac river. In the last rain, of the many that occurred throughout its history [French Institute of Andean Studies], on April 5, 2012 it received 37 liters of water per square meter for 30 minutes (Senamhi report), a fact that oversaturated the surface of the 100,000 m3 of loose materials, which have a heterogeneous granulometry, and gave rise to a flow of debris. To prevent and mitigate similar natural phenomena from recurring, we have designed energy dispersers based on reinforced concrete: f'c '= 210 kg / cm2, one of which has been partially built similar to the five already existing in the small streams located in the east sector, which are cyclopean concrete. Energy dispersers reduce the speed of water and retain large rocks, they are proposed walls perpendicular to the axis of the creek. Our proposal is for four reinforced concrete structures, length equal to the width of the torrent, 3 m high on the axis of the ravine, 0.70 m at the top. The edges of these walls are rounded and reinforced, iron mesh of Ø 1 ”every 20 cm, in two vertical meshes and two horizontal meshes, in addition more trees and bushes will be installed in the study area in addition to the existing ones, such such as: molles, guarangos, pines, eucalyptus, pacayes, pomegranates, willows and oaks.